Learning Motivation of Primary Students about Online Learning Management - Lakkhana Panit; Prasart Nuangchalerm (Universitas Sultan Ageng Tirtayasa, 2022)
This research aimed to study the motivation of primary students about online learning during COVID-19 pandemic. Informant group includes 159 primary school students from one school, academic year 2021. Research tool used questionnaire on factors affecting to motivation in online learning during COVID-19 pandemic. Statistics used to analyze data were mean and standard deviation. The results showed that students were high level of high motivation in most factors, but the learning materials and attitude towards online learning were at moderate level. Teachers and school administrators need to find proper practices to deal with online learning and students’ learning motivation as well as new normal schooling. The guideline for motivating students to engage online classroom need to be discussed and generate new normal classroom environments.